A study of safety level for UiTM Shah Alam student / Khairul Ridhwan Rozak - Rozak, Khairul Ridhwan (Faculty of Architecture, Planning and Surveying, 2013)
Safety is the “safe” condition is being protected against physical, social nature, spiritual, financial, political, emotional, occupational, psychological, educational or other from the failure, defect, error, accidents, harm or any other person events that may be improper. Safety can also be defined as a recognized hazard control in order to achieve acceptable levels of risk. This can take the form has been protected from the event or from exposure to something that causes health or economic losses. It can include protection of persons or property. The other word it means the condition of being safe or freedom from danger, risk or injury. In this study, UiTM has been chosen as the venue for the case study. Some of the areas selected for data collection is Sultan Abdul Aziz Tower (SAAS Tower), Tower Engineering Science & Technology (S & T Tower), Rose College, Orchid College, Lotus College and Perindu College. The purpose of this study is to achieve the objectives that have been made. The objective of this study was to study the type of safety provided in item ,to evaluate the level of safety for students in UiTM and to investigate the factor that contributes to the safety level to students in UiTM.